Assessment and spatiotemporal analysis of global flood vulnerability in 2005–2020. (1st October 2022) - Duan, Yu; Xiong, Junnan; Cheng, Weiming; Wang, Nan; He, Wen; He, Yufeng; Liu, Jun; Yang, Gang; Wang, Jiyan; Yang, Jiawei
Abstract: The impacts of flood disasters on human society have been attracting increasing attention in recent years. Despite significant improvements in the modeling of flood hazard and exposure, compelling evidence of the spatial and temporal patterns of social vulnerability around the world is still lacking. In this study, a global flood vulnerability (FV) framework that simultaneously considers exposure, sensitivity, and coping capacity was developed. Then, the spatiotemporal distribution of the FV was determined based on game theory (GT), and the FV value was integrated with the regional integrated FV grades (RIFVG) at the global, continental, and national scales. The results reveal that: (1) The global FV exhibits a U-shaped trend, i.e., decreasing and then increasing (RIFVG changing from 1.1643 to 1.1542, 1.1491, and 1.1795) during 2005–2020; (2) Great spatial heterogeneity exists between continents. Specifically, Asia and Europe are the two continents with the highest RIFVG values, and the losses to floods may rise significantly in Africa in the future; (3) The high vulnerability areas are mainly distributed in areas and countries with dense populations and developed economies (i.e., eastern China and northern India). In addition, more than half of the 20 countries with the highest RIFVG values are developed countries; (4) As the frequency and magnitude of global floods are likely to increase under climate change, significant inequalities between low-income and high-income countries remain and even deepen. The results of this study can provide scientific and technological basis for decision makers to formulate disaster prevention and mitigation policies. Graphical abstract: Image 1 Highlights: A new combined GT approach is proposed based on TFN-AHP and EM. The relationships between exposure, sensitivity, and coping capacity are considered. Multiscale spatiotemporal analysis of FV with a higher resolution is conducted. Potential causes and influences behind global FV and its patterns are revealed.